2010
DOI: 10.1177/1043659609360849
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture, Quality of Work Life, and Organizational Effectiveness in Korean University Hospitals

Abstract: Intact organizational culture and quality of work life for nurses will undoubtedly lead to improved organizational effectiveness. Without efficient and effective nursing care, desired patient outcomes cannot be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 18 publications
0
27
0
7
Order By: Relevance
“…This issue should be considered by human resources administrators. In this vein, we must emphasize that establishing programs to improve quality of life in the workplace for the nursing staff can improve organizational effectiveness because quality of life is a predictor of this effectiveness 14 . Accordingly, attending to the needs of the nursing staff should be a priority for the healthcare system because it represents a quality standard that has direct repercussions for the people receiving care.…”
Section: Discussionmentioning
confidence: 99%
“…This issue should be considered by human resources administrators. In this vein, we must emphasize that establishing programs to improve quality of life in the workplace for the nursing staff can improve organizational effectiveness because quality of life is a predictor of this effectiveness 14 . Accordingly, attending to the needs of the nursing staff should be a priority for the healthcare system because it represents a quality standard that has direct repercussions for the people receiving care.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that these issues arising from the QWL may potentially affect organizational culture and effectiveness, staff 's health and patients' morbidity and mortality rates (An, Yom, & Ruggiero, 2011;Cole et al, 2005;Laschinger, Finegan, Shamian, & Almost, 2001). Low effectiveness and quality of health care services provided by nurses, more complaints, and higher direct medical expenses have been noted as the repercussions of low levels of QWL (Sirgy et al, 2001).…”
Section: The Importance Of Qwl In Nursingmentioning
confidence: 97%
“…A QVT de docentes em instituições de ensino também desperta forte interesse dos estudos organizacionais, tanto de pesquisadores nacionais (KOETZ; REMPEL; PÉRICO, 2013: PIZZIO;KLEIN, 2015;SOUZA et al, 2015;LIMA;LIMA-FILHO, 2009), quanto internacionais (HART, 1994; JI-YOUNG AN; YOUNG-HEE YON; RUGGIERO, 2010;JAIN;THOMAS, 2016). Hart (1994), já pesquisava as experiências de QVT em instituições de ensino e em investigação com 1539 docentes australianos, constatou que o sofrimento psíquico e o moral contribuem igualmente para a QVT.…”
Section: Qualidade De Vida No Trabalho: Aspectos Conceituais E Em Insunclassified